Sifat Fisik Daging Kelinci Peranakan New Zealand White Yang Diberi Ransum Mengandung Tepung Kulit Pisang Kepok (Musa paradisiaca L.) - D Hermawan; Z Zairiful; D D Putri (PETERPAN (Jurnal Peternakan Terapan), 2021)
This study aims to analyze the effect of Kepok banana peel flour (Musa acuminata x Musa balbisiana) in the ration on the physical of New Zealand White crossbreed rabbits meat. This research was conducted in the rabbit cage of Lampung State Polytechnic with 20 male rabbits of the New Zealand White breed aged 2 months. The experiment was carried out with an experimental method, using a completely randomized design (CRD), with 5 treatments and 4 replications. The treatments used in this study were P0: 100% commercial feed, P1: 98% commercial feed + 2% kepok banana peel flour, P2: 96% commercial feed + 4% kepok banana peel flour, P3: 94% commercial feed + 6 % Kepok banana peel flour, P4: 92% commercial feed + 8% Kepok banana peel flour. The results of statistical analysis showed that the pH value of the meat, cooking loss and tenderness of the meat had a significant effect. The results of statistical analysis showed that the value of the water holding capacity had no significant effect. The conclusion of this study is that feed fed with Kepok banana peel flour has a significant effect on the physical of New Zealand White crossbreed rabbit meat including the pH value of the meat with the lowest value of 5.70, at 2% treatment, loss of cooking meat with a value of 35.00 (% ) was found in treatment 4%, and meat tenderness with a value of 3.30 (gf) at 4% treatment and 3.20 (gf) at treatment 8%. However, it has no significant effect on water holding capacity.